Facing Two Ways Syntactically: On the Grammar and Use of Promise and Threaten in Three Regional Varieties - Rickman, Paul; Rudanko, Juhani (English studies, 2023)
The predicates promise and threaten with a to infinitive complement can be used in two main senses, with each sense representing a different argument structure: subject control, and subject to subject raising. Recent work has shown both uses to have been available for several centuries, with the raising variant emerging later than the control. The present investigation aims to provide insight into the usage patterns of the two predicates in the Englishes of New Zealand, Britain, and North America. The former is compared to the two latter varieties to help further our understanding of the complex system of the grammar of English predicate complementation. The data is examined from quantitative and qualitative perspectives, and the results indicate not only significant variation in usage among the varieties, but also high levels of correlation in some areas. New findings emerge from the study, including on the notion of stance, offering fresh avenues of research into the nature of the complementation patterns examined and their use in three core varieties of English.